Kandungan Bakteri Asam Laktat pada Sourdough Air Fermentasi Nanas dan Pengaruhnya terhadap Mutu Tekstur Roti Tepung Beras - Agustina, Nia; Haris, Helmi (JURNAL AGROINDUSTRI HALAL, 2025)
This study aimed to evaluate the utilization of pineapple fruit fermentation water as a natural starter in sourdough production and its effect on the textural properties of rice-based bread. The fermentation water was prepared from a mixture of pineapple, water, and sugar, and fermented at 30°C for 48 hours until reaching optimum microbial activity. The resulting sourdough was then applied in bread making using rice flour as the main ingredient, combined with tapioca and potato flours. The experimental design used a Completely Randomized Design with three treatments, namely control bread (commercial yeast), water-based sourdough bread, and pineapple sourdough bread, each repeated three times. Observed parameters included pH, titratable acidity, lactic acid bacteria and yeast counts, specific volume, crumb microstructure, and bread texture. The results showed that pineapple fermentation water supported the growth of lactic acid bacteria and yeast, reaching the highest population at 48 hours, indicated by a decrease in pH and an increase in acidity. Pineapple sourdough bread exhibited higher hardness, gumminess, and chewiness compared to the control and water sourdough bread, but maintained good springiness, resulting in a softer crumb structure that was not brittle. In conclusion, pineapple fermentation water can serve as a promising natural starter to improve the quality and texture of gluten-free rice bread.